Ultrasound Elastography in Evaluation of Peripheral Pulmonary Lesions - Rouf, Abdul; Debi, Uma; Devkota, Shritik; Garg, Mandeep; Singh, Navneet; Bal, Amanjit; Bhujade, Harish; Prasad, K. T. (Acta medica Lituanica, 2026)
Background: Differentiating benign from malignant peripheral pulmonary lesions (PPLs) remains a clinical challenge, especially in resource-limited settings. While computed tomography is the standard imaging modality, it involves radiation exposure and often lacks specificity. Shear Wave Elastography (SWE) is a non-invasive ultrasound technique that quantifies tissue stiffness and may aid in the evaluation of PPLs.Methods: In this prospective observational study, 42 patients with peripheral pulmonary lesions underwent transthoracic SWE prior to histopathological evaluation. Elastography values were compared between benign and malignant lesions. Statistical analysis included ROC curve assessment, logistic regression, and correlation with histopathological and microbiological outcomes.Results: Of the 42 patients, 64.3% had malignant and 35.7% had benign lesions. The mean SWE value for malignant lesions was significantly higher (6.82 ± 2.27 kPa) than for benign lesions (3.72 ± 2.23 kPa; p
Keywords: ultrasound elastography; SWE; elastography; lung lesions